Pertanggungjawaban Negara China Akibat Pencemaran Di Laut China Selatan Dalam Prespektif Hukum Lingkungan Internasional - Jenesya Susye Matakena; Marthinus Kainama; Veriana Josepha Batseba Rehatta (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: One of the satellite imagery analysis companies, Head Of Simularty, based in the United States, found that there has been pollution to the marine environment in the South China Sea area, precisely in the Spratly Islands, namely the coral island of Whitsun Reef which is still part of the Exclusive Economic Zone of the Philippines.Purposes of the Research: Aims to find out and analyze the regulation of international law on pollution in the South China Sea and to find out and analyze the form of accountability of the Chinese State due to marine pollution carried out under international environmental law. Methods of the Research: This legal research uses normative juridical research, case approach, statutory approach, and conceptual approach, primary and secondary legal materials, legal material procedures using primary legal materials which are then associated with secondary legal materials and processing and analysis of legal materials using qualitative descriptive analysis.Results of the Research: The results showed that China had violated international environmental law obligations as stipulated in the Stockholm Declaration 1972, Rio Declaration 1992, UNCLOS 1982 and MARPOL 73/78. Furthermore, marine pollution carried out by the State of China in the territory of the Exclusive Economic Zone of the Philippine State has opposed the provisions of international environmental law as stipulated in the 1972 Stokcholm Declaration and UNCLOS 1982 which states that it prohibits any country from taking acts of pollution against the environment against both its own territory and in the jurisdiction of other countries. Therefore, it is necessary to have accountability efforts that must be carried out due to the pollution actions carried out.